2005
DOI: 10.1002/hed.20332
|View full text |Cite
|
Sign up to set email alerts
|

Intensity‐modulated radiation therapy in head and neck cancers: An update

Abstract: Intensity-modulated radiation therapy (IMRT), an advent of three-dimensional conformal radiotherapy (3D CRT), has excited the profession of radiation oncology more than any other new invention since the introduction of the linear accelerator. Approximately 1000 articles have been published on this topic to date, more than 200 of which focus on head and neck cancer. IMRT is based on computer-optimized treatment planning and a computer-controlled treatment delivery system. The computer-driven technology generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
149
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(152 citation statements)
references
References 58 publications
0
149
0
3
Order By: Relevance
“…Therefore, improving radiotherapy may allow reduction of this complication. Intensity-modulated radiotherapy (IMRT) has been widely used for head and neck cancers [17]. Using this advanced technique, complications can now be reduced without compromising therapeutic outcome [18].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, improving radiotherapy may allow reduction of this complication. Intensity-modulated radiotherapy (IMRT) has been widely used for head and neck cancers [17]. Using this advanced technique, complications can now be reduced without compromising therapeutic outcome [18].…”
Section: Discussionmentioning
confidence: 99%
“…The target volumes are surrounded by critical normal tissue structures and may comprise some hundred milliliters when including lymph nodes and/or lymphatic pathways. Conformal dose distributions are typically provided by advanced photon therapy techniques like intensity‐modulated radiotherapy (IMRT) 1. While intensity‐modulated proton therapy (IMPT) can more effectively reduce the dose to healthy tissue2, 3, 4, 5 and thus allow for further dose escalation,6 proton beams are prone to range uncertainties if the penetrated tissue changes during therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown significant improvement in tumor targeting and normal tissue sparing, thus improving local control and reducing toxicity rates. [11][12][13][14] IMRT has now become the standard of care in select adult malignancies, including head and neck cancers, 11 gastrointestinal malignancies (eg, esophageal, 12 anal cancer 13 ), and prostate cancer. 14 Although these techniques can significantly reduce the dose delivered to normal tissues, both acute and late toxicities remain a concern.…”
Section: Basic Proton Dosimetrymentioning
confidence: 99%
“…14 Although these techniques can significantly reduce the dose delivered to normal tissues, both acute and late toxicities remain a concern. [11][12][13][14] The pattern of dose deposition in proton particles differs from that of photons and electrons. As the proton beam travels through tissue and maintains velocity and energy, it begins to slow near the end of its path.…”
Section: Basic Proton Dosimetrymentioning
confidence: 99%